Curriculum Differentiation Practice: A Case Study of Visual Impairments - G.C., Krishna Bahadur (The Educator Journal, 2024)
Curriculum signifies a holistic plan including the objectives, content, strategy, and assessment system. It is the backbone of the inclusive education system of the nation. Everyone has the right to education from the perspective of human rights and child rights. There are diverse backgrounds in the classrooms of Nepalese schools. One of the diversity is visual impairments. Visual impairment can be caused by loss of vision, causing the eyes not to be able to see objects as clearly as usual. It can also be due to visual field loss, which makes it impossible to see a wide area as usual without moving the eyes or turning the head. To secure their rights, the nation provides the proper education. Curriculum differentiation practice is one of the best ways to inclusive process. Regarding this, exploring the present practice of curriculum differentiation and exploring its major problems are objectives of the research which provide guidelines to complete the study. With the support of socio-cultural theory and multiple intelligence theory, this research is held. A qualitative case study approach based on this study including interview and non-participation observation techniques of information generation explores the real practice of curriculum differentiation in the case of visual impairments. Lack of proper training, resources, culturally reflected curricula, and traditional assessment systems are some problems of differentiated practice where the braille script, assistive technology, individualized educational plans and peer support, and inclusive practice along with sensitization and awareness are some better practices of it. To reduce the barrier of differentiated practice, regular teacher training, increasing participation ofstakeholdersin the curriculum development process, resource allocation, and the assessment system should be reformed. By doing it the curriculum’s differentiated practice ensures inclusion.